2013
DOI: 10.1007/s10533-013-9883-8
|View full text |Cite
|
Sign up to set email alerts
|

The importance of denitrification for N2O emissions from an N-saturated forest in SW China: results from in situ 15N labeling experiments

Abstract: ) were applied as a single dose to replicated plots at two positions along the hill slope (at top and bottom, respectively) during monsoonal summer. During a 6-day period after label application, we found that 71-100 % of the emitted N 2 O was derived from the labeled NO 3 -pool irrespective of slope position. Based on this, we assume that denitrification is the dominant process of N 2 O formation in these forest soils. Within 6 days after label addition, the fraction of the added 15 N-NO 3 -emitted as 15 N-N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 47 publications
5
34
1
Order By: Relevance
“…The positive correlation is consistent with other findings by Papen andButterbach-Bahl (1999), andYuping et al (2008). N 2 O flux was positively correlated with soil moisture content (%), which is in good agreement with other studies (Lemke et al, 1998;Rafique et al, 2011;Zhu et al, 2013a). Greater N 2 O emissions during rainy season at both landuses were associated with higher soil moisture content that enhance microbial activity.…”
Section: Discussionsupporting
confidence: 91%
“…The positive correlation is consistent with other findings by Papen andButterbach-Bahl (1999), andYuping et al (2008). N 2 O flux was positively correlated with soil moisture content (%), which is in good agreement with other studies (Lemke et al, 1998;Rafique et al, 2011;Zhu et al, 2013a). Greater N 2 O emissions during rainy season at both landuses were associated with higher soil moisture content that enhance microbial activity.…”
Section: Discussionsupporting
confidence: 91%
“…The 15 N abundance of NH 4 + was not measured in this study since the high NO 3 − content in our soil and no extra organic carbon was added; the process of dissimilatory NO 3 − reduction to NH 4 + could be neglected (Zhu et al 2013). Moreover, NH 4 + concentrations in the soil extracts were too low to make a dependable determination of the 15 N enrichment.…”
Section: Calculations and Statisticsmentioning
confidence: 92%
“…One of our previous results demonstrated that a high level of NH 4 Cl addition significantly led to soil NO 3 À accumulation, which indirectly indicates a high O 2 consumption caused by a high nitrification rate [23]. Using 15 N-tracing experiment and 15 N-tracing models, denitrification was believed to be the largest source of N 2 O flux relative to nitrification and other N transformations in the subtropical forest soils [58,59]. On the other hand, accelerated nitrification by NH 4 þ additions gradually decreased soil pH, which would result in higher N 2 O/N 2 ratio during soil denitrification [60].…”
Section: Linkages Between Soil Ch 4 and N 2 O Fluxes And Ammoniaoxidimentioning
confidence: 93%